The meaning of manageable neuropathic pain after SCI - Marlon L. Wong; Kimberly D. Anderson; Kathryn E. Roach; Linda Robayo; Nicholas P. Cherup; Roberta Vastano; Gabriel Fernandez; Eva Widerström-Noga (Frontiers in Pain Research)
IntroductionChronic neuropathic pain (NP) is a prevalent and debilitating condition among individuals with spinal cord injury (SCI). Complete pain relief is often unattainable, making the concept of “manageable pain” a critical focus for improving quality of life. This study aims to elucidate the meaning of manageable pain for individuals with chronic NP post-SCI.MethodsA mixed-methods approach was employed, involving qualitative interviews and quantitative assessments with 36 participants experiencing moderate to severe NP.ResultsThe qualitative data revealed three major themes: Manageable Pain, Unmanageable Pain, and Ways to Control Pain. Manageable pain was characterized by its moderate intensity, predictability, and minimal interference with daily activities. In contrast, unmanageable pain was associated with significant emotional distress, activity hindrance, and inability to control the pain. Participants used a variety of techniques to control pain, including cognitive/emotional coping strategies, medication, and physical activity. Most participants used a multimodal approach that was severity and situation dependent.DiscussionThese findings underscore the multifaceted nature of pain management and the importance of individualized approaches that consider both pain acceptance and coping strategies. This study provides valuable insights into the personal experiences of NP in people with SCI and their perspectives on the meaning of manageable pain. These findings highlight the need for comprehensive pain management strategies that enhance daily functioning and overall well-being.